Electroencephalographical correlates of cortex stage of sensory citric acid perception - Savaneuskaya, Alena M. (Experimental Biology and Biotechnology, 2019)
The article deals with the methodological problem faced while identifying the EEG-correlate of taste sense by perception of complex stimuli involving a wide spectrum of sensory systems. As an example we defined a brain cortex activity pattern by tasting citric acid. As a result most promising taste perception correlate was found in beta high frequency band of right frontal cortex area. Other loci of brain cortex activity observed by citric acid presentation reflect non-taste perception forms appearing as by-products of oral stimulation.